2015
DOI: 10.1158/0008-5472.can-14-0350
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 Is a Key Regulator of Cancer-Associated Fibroblasts

Abstract: Cancer-associated fibroblasts (CAF) are key contributors to malignant progression, but their critical regulators remain largely unknown. In this study, we examined the role of Twist1, a central regulator of epithelial–mesenchymal transition in carcinoma cells, in the transdifferentiation of normal quiescent fibroblasts to CAF and we defined its upstream controls and downstream effectors. Primary human gastric fibroblast and CAF cultures were established from gastrectomy specimens and validated as nontumor cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 46 publications
8
111
0
Order By: Relevance
“…Interestingly, the authors noted that the mechanotransduction pathways regulating TWIST1 were, like SNAIL1, distinct from YAP regulation. In that work, CAFs were not examined; however, another report studying gastric cancer CAFs has found that TWIST1 is important for the differentiation of normal tissue fibroblasts into CAFs (Lee et al, 2015). We also noted that TWIST1 protein levels increased as fibroblasts evolved from normal tissue fibroblasts to CAFs (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, the authors noted that the mechanotransduction pathways regulating TWIST1 were, like SNAIL1, distinct from YAP regulation. In that work, CAFs were not examined; however, another report studying gastric cancer CAFs has found that TWIST1 is important for the differentiation of normal tissue fibroblasts into CAFs (Lee et al, 2015). We also noted that TWIST1 protein levels increased as fibroblasts evolved from normal tissue fibroblasts to CAFs (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…Through CXCR4, a receptor of CXCL12, signaling pathway in cancer cells, secretion of CXCL12 by CAFs induces epithelial-mesenchymal transition of cancer cells in gastric and prostate cancers [18][19], migration and metastasis in prostate cancer [20], and tumor growth in breast cancer [21].…”
Section: 3-1 Tumor-promoting Mechanisms Of Cafsmentioning
confidence: 99%
“…mCAFs, especially those isolated from the interface zone of breast tumors, are claimed to be a robust inducer of EMT [94,95]. With respect to the molecular mechanism, many mediators, such as Twist1 [96], SDF-1 [97] and the SNAIL family [51], were identified. Cycloxygenase-2 (COX-2)/nuclear factor-kappa B (NFκB)/hypoxiainducible factor-1 (HIF-1) signaling, and TGFβ, ERK, JUN and RHO signaling are thought to be responsible for mCAF-induced EMT [68,94,95,[98][99][100].…”
Section: Mcafs Drive Cancer Cell Migration Invasion and Metastasismentioning
confidence: 99%